The Influence of Education and Training on Employee Career Development at PT. Asam Jawa Medan - Hegy Maylisa Sijabat; Nalom Siagian; Vera A. R. Pasaribu (Pendidikan Islam Anak Usia Dini STIT Palapa Nusantara, 2026)
Driven by the scarcity of empirical studies on specific competency determinants in the plantation industry, this study examines the impact of education and training on career advancement at PT. Asam Jawa Medan. Initial observations revealed a mismatch between employees’ educational qualifications and job requirements, as well as inconsistency in the implementation of training programs. Adopting a quantitative design, the study involved 52 respondents selected through purposive sampling, with data collected via structured questionnaires and analyzed using multiple linear regression in SPSS. The results show that both education and training have a positive and significant effect on career development, and that their combined influence explains 50.5% of the variance in employees’ career growth. These findings align with established human resource management theories and confirm that enhancing the quality of education and the effectiveness of training initiatives is critical for supporting career mobility in the plantation sector. The study concludes that organizations should raise recruitment standards, strengthen technical training, and implement transparent promotion systems to better align competencies with career pathways. Theoretically, the research contributes to the human resource management literature on career development, while practically it offers guidance for HR policy refinement and identifies avenues for future research on additional determinants such as work motivation, leadership, and organizational culture.